Deaths due to methanol poisoning: forensic autopsy series - Sancı, Abdulkadir; Kaya, Burak; Taşdemir Sancı, Gülşen (Journal of Dependence, 2025)
Methyl alcohol is a substance often associated with toxic effects and fatalities due to its use in the production of counterfeit alcohol. The primary mechanism of poisoning occurs when it is metabolized in the body by the enzyme alcohol dehydrogenase, resulting in the formation of formic acid. This formic acid can lead to metabolic acidosis, loss of vision, and neurological damage because of its strong toxic effects. Symptoms of poisoning may include vomiting, headache, cyanosis, and "blizzard vision." In such cases, the typical cause of death is acidosis, and the formation of formic acid can be mitigated by using ethyl alcohol as treatment. In forensic autopsies, the cause of death resulting from methanol poisoning, the method of ingestion, and the quantity consumed are determined through toxicological analysis. This study presents four cases of death due to methanol poisoning from the Artvin Forensic Medicine Branch Directorate and emphasizes the need to raise awareness, develop effective public health policies, and implement comprehensive measures to protect public health.